EQUIVALENCE AND NON-INFERIORITY TRIALS IN A SNAPSHOT - Kerai, Salima (Journal of Ayub Medical College Abbottabad, 2017)
Randomized controlled trials conventionally entails superiority hypothesis where researcher is interested to know whether a new treatment is better than the standard of care. However, developing and testing novel techniques or therapies which are better than standard is not always feasible. There are circumstances when effective treatment exists and new treatment is not substantially better than existing treatment and conducting placebo controlled trials are unethical. Then goal of the investigator changes; if new treatment is equivalent or non-inferior in comparison to current standard of care with respect to a-priori set endpoints. The current paper aims to discuss few key principles of equivalence and non-inferiority trial design and some challenges to think about before designing or conducting these trials. Keywords: Equivalence trials, Non-inferiority trials